The Correlation of The Mixed Layer Depth with La Nina and El Nino Index In The Natuna Basin - Aji, Tri; Pranowo, Widodo Setiyo; Asmoro, Nuki Widi; Agustinus, Agustinus; Kurniawan, Muhammad Azis; Rahmatullah, Amri (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
The Natuna Sea is one of the seas located in the northern part of Indonesia, which is influenced by several oceanographic climate phenomena, including the El Nino-Southern Oscillation (ENSO) system, such as La Nina and El Nino, which cause vertical temperature dynamics. This study aimed to examine the relationship between La Nina, El Nino, and normal years on the variability of the mixed layer depth in the Natuna Sea. The study utilized temperature data from the World Ocean Database (WOD) and Marine Copernicus for a period of 3 years, including years with La Nina, El Nino, and normal conditions, as well as mixed layer depth (defined by sigma theta) data from Marine Copernicus. the occurrence of La Nina, El Nino and normal years obtained from the Southern Oscillation Index (SOI). The results showed that the correlation of SOI values with the depth of Maximum Mix Layer Depth (MLD) during El Nino and La Nina was weak and very weak during the Normal year. During the La Nina, normal, and El Nino periods, the deepest MLD occurred during the west monsoon season at depths ranging from 7 to 60 meters. The shallowest MLD occurred during the first transition season at depths ranging from 7 to 25 meters. The MLD values during the east monsoon season depths ranging from 7 to 43 meters, and during the second transition season, the MLD ranges from 7 to 44 meters.